Deviant Behaviour and Students’ Academic Activities in Oyo State, Nigeria - Oladipo, Ileola Elizabeth; Udoh-Emokhare, Christine Ekojoka; Oladipo, Temidayo David (African Journal of Stability and Development (AJSD), 2023)
Education remains one of the tools for the transformation of individuals and society. It is a powerful instrument of social change, which also plays a crucial role in nation-building. The rate of involvement of in-school adolescents in deviant behaviour is however of great concern to stakeholders. Indiscipline in schools has reached an alarming rate; a situation which could be traced to the home, society and the attitude of students towards schooling. The result is poor academic performance of many in-school adolescents. This study becomes necessary in the light of anti-social deviant behaviours among in-school adolescents in Nigeria. The main purpose of the study was to investigate the influence of deviant behaviour on academic activities and identify the strategies for managing deviant behaviour among in-school adolescents using Oyo State, Nigeria, as a case study. The findings show that there was a significant relationship between deviant behaviours and students’ academic activities. There was also a common consensus of high incidences of physical, verbal, and academic related deviant behaviours. Results of the study revealed three factors- parent, society and school- that contribute to deviant behaviour. To address the effect of deviant behaviour affecting the educational system in Nigeria therefore, the study identified administrative advancement, parental influence/control as well as counselling as measures that government, parent and other stakeholders can adopt to improve educational outcomes.